Efek Glycine max Varietas Anjasmoro terhadap Kadar Timbal dan Malondialdehid pada Mencit Terintoksikasi Timbal - Yulia, Rika; Karina, Lidya; Veronica, .; Christyaningsih, Juliana (Indonesian Research Gateway)
The objective of this research is investigating the effect of Glycine max Anjasmoro variety to mice with lead intoxication by measuring the levels of Pb in mice's (Mus musculus) blood and MDA in mice's liver and kidney strain BALB/C by using the thiobarbituric acid reactive substance (TBARS) assay. Research carried out by using 20 mice strain BALB/C that were randomly divided into four groups of five mice including negative control, positive control, treatment, and reference. All groups except positive control were intoxicated with lead in a dose of 25 mg/kg body weight for the duration of seven days. One gram of Glycine max has been given to the treatment group and positive control. There after 64 mg/kg body weight of vitamin has been given to the reference group. The results showed that Glycine max Anjasmoro varieties was significantly decrease the levels of lead in mice's blood and also reduce the levels of MDA in the liver and kidney although the results were not significant.Keywords : Glycine max Anjasmoro variety, lead, malondialdehyde, vitamin C, Mus musculus